An integrated framework of generating quizzes based on linked data and its application on medical education field. (1st January 2021) - Shi, Wei; Ma, Chenguang; Yamamura, Hikaru; Kaneko, Kosuke; Okada, Yoshihiro
E-learning has greatly developed in recent years because of the popularity of smartphones and tablets. Because of the improvement of the device performances and the data transmission capability of the internet, more and more complex e-learning materials are provided to learners. Quiz games are a kind of e-learning format which can both test and train learners. How to automatically generate 'good' quizzes is discussed by many researchers. In this paper, we proposed a new framework which can support users to create quiz games based on Linked Data. Linked Data stores both the values and the linkages among values. The quizzes generated by our framework are easy to improve and extend, have more changes, and support the learning analytics of users' activities. For obtaining better educational effects, we further extend our framework for supporting the generation of quizzes in 3D environments. Especially, we discuss how to apply our framework in medical education.